Pemulihan Balita Stunting Melalui Kemitraan Lintas Sektor - Arumsari, Wahyuni; Rarastiti, Chairunisa Nur; Rahayu, Sri; Sudrajat, Agus; Triwahyuni, Yeni (Borneo Community Health Service Journal, 2024)
The percentage of stunting in Semarang City in 2018 was 11.18%, while the Semarang targets is to fall to 4% in 2024. To accordance with this target, the Bambankerep Village Head's commitment is zero stunted in his area by 2024. The aim of the community service activities is to restore stunted toddlers in Bambankerep Village. The method used specific nutritional intervention and sensitive nutrition intervention accompanied by observation. Stunted toddlers who have been given intervention experience an increase in their z score to the normal category. The sectors involved in this research are PKK, Posyandu Cadres, Academics, Social Services, LPMK, Bhabinkamtibmas and the private sector. Each sector takes its own role in specific nutrition and nutrition sensitive interventions. In the future, more similar activities will be held by collaborating with other, more diverse sectors, such as the education sector.Â